Vacation under the volcano - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 1998)
Their magic tree house takes Annie and Jack to Pompeii just as Vesuvius is about to erupt, and they must find a Roman scroll before everything is covered with burning ash.
"A Stepping Stone book."
Keywords: Time travel; Tree houses